The Impact of Capital Adequacy Requirements on The Bank Risk-Taking Behavior - مرهج منذر; بعبع جمال (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The capital adequacy ratio is an international standard to indicate the strength of the bank’s financial position and this contributes to supporting the stability of the global banking system and remove the disparity in the ability of banks to compete and enhance the confidence of depositors from the perspective of deepening the solvency of the bank. From this point This research aims to study the effect of capital adequacy requirements on The bank Risk-Taking Behavior in private banks in Syria and the nature of this effect. The research community consists of private banks in Syria after the exception of Islamic banks from 2007 to 2018 and their number was / 11 / private banks. The study results showed There is statistically significant relationship between capital adequacy requirements and The bank Risk-Taking Behavior in private banks in Syria in that time period At a significant level of 5% . The results also showed a strong positive correlation between them, Where the capital adequacy rate explains 66% of the change in The bank Risk-Taking Behavior The research indicated that the Syrian private banking sector has a good commitment to the capital adequacy ratio standard.